2007
DOI: 10.1029/2005jd006571
|View full text |Cite
|
Sign up to set email alerts
|

Role of atmospheric circulation with respect to the interannual variability in the date of snow cover disappearance over northern latitudes between 1988 and 2003

Abstract: [1] This paper analyzes the main spatial patterns in the dates of snow cover disappearance variability over northern latitudes between 1988 and 2003. The dates of snow cover disappearance were calculated using satellite passive microwave data from the Special Sensor Microwave/Imager. Spatial and temporal patterns were obtained using principal components analysis in the S mode. We identified eight components, each representing a large region characterized by homogeneous interannual variability in the dates of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 130 publications
(188 reference statements)
1
12
0
Order By: Relevance
“…Conclusive evidence has been found to show that these changes are most pronounced at higher elevations, where the shifts in both onset and end dates of snow cover towards later and earlier dates, respectively, have also been observed. Several authors have linked these changes to an increasing trend in air temperature (Vicente‐Serrano et al , ; Choi et al , ; Brown and Robinson, ; Betts et al , ). They show that higher temperatures in November would delay the snow fall in autumn and higher temperatures during March–April would produce an earlier snowmelt.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusive evidence has been found to show that these changes are most pronounced at higher elevations, where the shifts in both onset and end dates of snow cover towards later and earlier dates, respectively, have also been observed. Several authors have linked these changes to an increasing trend in air temperature (Vicente‐Serrano et al , ; Choi et al , ; Brown and Robinson, ; Betts et al , ). They show that higher temperatures in November would delay the snow fall in autumn and higher temperatures during March–April would produce an earlier snowmelt.…”
Section: Discussionmentioning
confidence: 99%
“…Second, warm summer temperatures could accelerate development of early larval stages, reducing generation time from a two-year to one-year life cycle and increasing the number of mature beetles in any single year (Werner and Holsten 1985). Third, one to a few years of warm-phase ENSO during extended periods of cool-phase PDO interactions could extend the snow-free season through earlier snowmelt dates (Vincente-Serrano et al 2007), both facilitating earlier emergence and dispersal of beetles in the spring (Werner and Holsten 1985), and reducing soil moisture, thereby enhancing drought stress and the susceptibility of trees to beetle attack (Hard 1987, Barber et al 2000. In south-central Alaska, late-spring conditions are conducive for spruce beetle attack because the already depleted photosynthates required for production of defensive compounds are being put toward tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…(1) a tree ring record (MT index;1769-2003 (PDO index;1790-1979[D'Arrigo et al 2001) that reflects a measure of the variability in the dominant decadal mode of North Pacific average summer (April-August) SSTs (Mantua et al 1997). The ENSO index includes ENSO-sensitive tree ring records from subtropical North America calibrated on Niño-3 Pacific SSTs and accounts for 79% of variance in the instrumental record (1950( -1978).…”
Section: Spruce Beetle Outbreaks and Climatementioning
confidence: 99%
“…Based on satellite‐derived global snow cover data on weekly timescales, Bamzai [2003] showed that when the AO is anomalously high (low), continental‐scale snow extent anomalies are negative (positive). Recently, Vicente‐Serrano et al [2007] found that the variability in the date of snow cover disappearance was significantly related to the AO in western Siberia. In summary, models and instrumental data indicate a close link between the AO and snow at interannual to interdecadal timescales.…”
Section: Resultsmentioning
confidence: 99%